Gas–Liquid Slug Flow Studies in Microreactors: Effect of Nanoparticle Addition on Flow Pattern and Pressure Drop - Zong, Jie; Yue, Jun (Frontiers in Chemical Engineering, 2022)
Colloidal suspensions of nanoparticles (e.g., metals and oxides) have been considered as a promising working fluid in microreactors for achieving significant process intensification. Existing examples include their uses in microflow as catalysts for enhancing the reaction efficiency, or as additives to mix with the base fluid (i.e., to form the so-called nanofluids) for heat/mass transfer intensification. Thus, hydrodynamic characterization of such suspension flow in microreactors is of high importance for a rational design and operation of the system. In this work, experiments have been conducted to investigate the flow pattern and pressure drop characteristics under slug flow between N2 gas and colloidal suspensions in the presence of TiO2 or Al2O3 nanoparticles through polytetrafluoroethylene (PTFE) capillary microreactors. The base fluid consisted of water or its mixture with ethylene glycol. The slug flow pattern with nanoparticle addition was characterized by the presence of a lubricating liquid film around N2 bubbles, in contrast to the absence of liquid film in the case of N2-water slug flow. This shows that the addition of nanoparticles has changed the wall wetting property to be more hydrophilic. Furthermore, the measured pressure drop under N2-nanoparticle suspension slug flow is well described by the model of Kreutzer et al. (AIChE J 51(9):2428–2440, 2005) at the mixture Reynolds numbers ca. above 100, and is better predicted by the model of Warnier et al. (Microfluidics and Nanofluidics 8(1):33–45, 2010) at lower Reynolds numbers given a better consideration of the effect of film thickness and bubble velocity under such conditions in the latter model. Therefore, the employed nanoparticle suspension can be considered as a stable and pseudo single phase with proper fluid properties (e.g., viscosity and density) when it comes to the pressure drop estimation.